Pengaruh Stategi Problem Focused Coping Terhadap Distress Pada Penyandang Diabetes Melitus Di Wilayah Kerja Puskesmas Ngoresan Jebres - Erika Sitta Nurlaela; Okti Sri Purwanti (Universitas Muhammadiyah Surakarta, 2020)
Diabetes mellitus is a type of chronic disease, which has increased from year to year. When someone is diagnosed with diabetes, he is required to change his lifestyle and undergo routine treatment. Diabetes can be distress related to the disease. Solutions can be prevented and used using strategies Problem Focusing on Coping or direct problem-solving. The purpose of this study was to study whether there was an implementation of a problem-focused strategy to overcome DM difficulties in the Ngoresan Jebres health center work area. The type of this research is quantitative, quasi research method experiment with control group design is not equivalent. The study was conducted in the working area of Ngoresan Jebres Health Center in November 2018. The study sample was 30 respondents with 15 experimental groups and 15 control groups, the sampling technique used purposive sampling. The research instrument used the Diabetes Scale Distress questionnaire 17. Data processing techniques used a paired sample t-test. The results of the pre-test in the study showed 40% with moderate distress, and 60% with severe distress, while in the control group 87% with moderate distress and 13% with severe distress, after giving the results of the study the post-test showed that the experimental group 80% normal and 20% moderate difficulty, while in the control group it rose to 73% moderate difficulty and 27% severe difficulties. The average distress of the control group 259.47 rose to 264.47, while the experimental group before being given the Problem Focused Coping strategy of 301.80 rose to 179.47 with (p-value) 0,000